The Privatization of Global Environmental Governance: ISO 14000 and the Developing World - Jennifer Clapp (Environment in the New Global Economy: Volume II, 2003)
International environmental threats have commanded widespread attention since the late 1960s. A number of unprecedented environmental disasters have galvanized public concern, and have reached the international political agenda in part through the activities of new environmental social movements in the industrialized countries. Environment in the New Global Economy is designed as a reference source for both students, researchers and policymakers concerned with the political dimension of international environmental problems. Peter Haas has selected those previously published articles which are seminal in the development of this new field and which have either generated widespread debate or represent a clear application of major approaches to the understanding of these new issues. He has also provided an authoritative introduction to complement his selection.